Correlation between the gut microbiota composition and cognitive frailty: a case–control study in community-dwelling older adults - Wen, Nana; Zhang, Yu; Sun, Liwei; He, Jianquan; Zheng, Guohua (Frontiers in Nutrition, 2026)
BackgroundAlthough alterations in the gut microbiota have been documented in older adults with mild cognitive impairment or physical frailty, the relationship between gut microbiota changes and cognitive frailty (CF) which is a clinical syndrome characterized by the coexistence of physical frailty and mild cognitive impairment in the absence of any dementia, remains unclear. This study aimed to investigate the gut microbial composition associated with CF and to assess the differences between community-dwelling older adults with CF and those without CF using 16S rDNA gene sequencing.MethodsA case–control study was conducted in community-dwelling older adults. Thirty-five older adults with CF and an equal number of older adults without CF were recruited. Fecal samples were examined by 16S rDNA sequencing. Differences in microbial composition at various taxonomic levels between the two groups were identified and evaluated for correlations with cognitive or physical function.ResultsThe β-diversity differed significantly between the CF and non-CF groups. Several taxa were more abundant in the CF older adults, including the phylum Verrucomicrobia and Tenericutes, the class Verrucomicrobiae and Mollicutes, and three orders (e.g., Verrucomicrobiales), six families (e.g., Akkermansiaceae), and eight genera (e.g., Escherichia-shigella). In contrast, the orders Betaproteobacteriales and Pasteurellales, the families Burkholderiaceae and Pasteurellaceae, and the genera Roseburia and Haemophilus were more abundant in the non-CF older adults (all p < 0.05). Altered gut microbiota effectively discriminated CF older adults well from controls (AUC = 92%). Certain microbiota enriched in the CF older adults, such as Family_XIII and Lactobacillaceae, showed negative correlation with physical performance, while Lactobacillaceae was also negatively correlated with cognitive performance (p < 0.05). conversely, microbiota more abundant in the non-CF older adults, including the genera Roseburia and Burkholderiaceae, were positively correlated with physical performance, and genera Roseburia and Pasteurellaceae were positively correlated with cognitive performance (p < 0.05).ConclusionThis study provides insight into the role of altered gut microbiota in the pathogenesis of CF among community-dwelling older adults. Further longitudinal studies with larger sample sizes are needed to establish causal relationships.